2018
DOI: 10.1002/ange.201807814
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Methanol and Carbon Monoxide over H‐ZSM‐5 to Form Aromatics

Abstract: The conversion of methanol into aromatics over unmodified H-ZSM-5 zeoliteisgenerally not high because the hydrogen transfer reaction results in alkane formation. Now circa 80 %a romatics selectivity for the coupling reaction of methanol and carbon monoxide over H-ZSM-5 is reported. Carbonyl compounds and methyl-2-cyclopenten-1-ones (MCPOs), which were detected in the products and catalysts, respectively,are considered as intermediates.The latter species can be synthesized from the former species and olefins. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…The conversion of MeOAc over SAPO-34 catalysts is reported to give an initial product distribution similar to that formed from methanol, although the production of alkenes falls after only 10 min on stream at 400 °C [17]. We are not aware of any comparable study of MeOAc conversion over HZSM-5, although we note that coupling of CO and methanol over HZSM-5 is reported to form aromatic products, presumably via MeOAc [18]. The results presented above suggest that the major role of MeOAc is to promote catalyst deactivation.…”
Section: Reaction Monitoringmentioning
confidence: 83%
“…The conversion of MeOAc over SAPO-34 catalysts is reported to give an initial product distribution similar to that formed from methanol, although the production of alkenes falls after only 10 min on stream at 400 °C [17]. We are not aware of any comparable study of MeOAc conversion over HZSM-5, although we note that coupling of CO and methanol over HZSM-5 is reported to form aromatic products, presumably via MeOAc [18]. The results presented above suggest that the major role of MeOAc is to promote catalyst deactivation.…”
Section: Reaction Monitoringmentioning
confidence: 83%
“…This result points to a distinct role of CO in the MTO reaction, as reflected in the ongoing debate on whether CO is a co-catalyst or a stoichiometric reactant in the initiation of the dual-cycle MTO mechanism, 39 44 and in recent CH 3 OH and CO co-feed studies that demonstrated C insertion from CO in HC products over ZSM-5. 61 Complementary tests in which CO was co-fed with methanol over the Si-, Mg-, and Co-APO-18 catalysts, without H 2 co-feed, showed negligible impact on the activity and product distribution ( Figures S18–S20 ). These results suggest either that CO does not take part in the reaction under the conditions studied here or that the cavity-window structure of the AEI topology leads to a diffusivity-dominated steady-state HC pool composition that masks its contribution in the absence of H 2 co-feed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In order to gure out the exact factors that promote the CO conversion and the synthesis of valuable aromatics, we performed the tandem syngas conversion on the bifunctional catalyst Recently, Chen et al reported that high-pressure CO participates in the methanol conversion process via the carbonylation reaction on the H-ZSM-5 catalyst. 37 Combined with the variation of CO conversion aer Ga doping, we speculated that the doping Ga species, especially the framework cationic Ga species, will affect the reaction network by changing the capability of CO to be inserted into the intermediates during the methanol to aromatics (MTA) conversion process. In order to verify this hypothesis, MTA conversion catalyzed by H/Ga-ZSM-5@SiO 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%